The contribution of Multi-GNSS Experiment (MGEX) to precise point positioning - Guo, Fei; Li, Xingxing; Zhang, Xiaohong; Wang, Jinling (Advances in space research, 2017)
In response to the changing world of GNSS, the International GNSS Service (IGS) has initiated the Multi-GNSS Experiment (MGEX). As part of the MGEX project, initial precise orbit and clock products have been released for public use, which are the key prerequisites for multi-GNSS precise point positioning (PPP). In particular, precise orbits and clocks at intervals of 5min and 30s are presently available for the new emerging systems. This paper investigates the benefits of multi-GNSS for PPP. Firstly, orbit and clock consistency tests (between different providers) were performed for GPS, GLONASS, Galileo and BeiDou. In general, the differences of GPS are, respectively, 1.0–1.5cm for orbit and 0.1ns for clock. The consistency of GLONASS is worse than GPS by a factor of 2–3, i.e. 2–4cm for orbit and 0.2ns for clock. However, the corresponding differences of Galileo and BeiDou are significantly larger than those of GPS and GLONASS, particularly for the BeiDou GEO satellites. Galileo as well as BeiDou IGSO/MEO products have a consistency of 0.1–0.2m for orbit, and 0.2–0.3ns for clock. As to BeiDou GEO satellites, the difference of their orbits reaches 3–4m in along-track, 0.5–0.6m in cross-track, and 0.2–0.3m in the radial directions, together with an average RMS of 0.6ns for clock. Furthermore, the short-term stability of multi-GNSS clocks was analyzed by Allan deviation. Results show that clock stability of the onboard GNSS is highly dependent on the satellites generations, operational lifetime, orbit types, and frequency standards. Finally, kinematic PPP tests were conducted to investigate the contribution of multi-GNSS and higher rate clock corrections. As expected, the positioning accuracy as well as convergence speed benefit from the fusion of multi-GNSS and higher rate of precise clock corrections. The multi-GNSS PPP improves the positioning accuracy by 10–20%, 40–60%, and 60–80% relative to the GPS-, GLONASS-, and BeiDou-only PPP. The usage of 30s interval clock products decreases interpolation errors, and the positioning accuracy is improved by an average of 30–50% for the all the cases except for the BeiDou-only PPP.